Ensuring Emergency Preparedness through Systematic Evaluations. Issue Volume 34:Issue s1(2019) (May 2019) - Margalit, Gila; Rachaminov, Orna; Levy, Yuval; Adini, Bruria; Grinberg, Amir
Abstract : Introduction: Hospitals are required to maintain emergency preparedness 24/7. In order to maintain readiness, Israeli hospitals operate Emergency Committees comprised of medical, nursing, and administrative professionals who are responsible for capacity building including the development of plans, infrastructure, equipment, training, crisis management, and learning lessons. The Ministry of Health (MOH) and Home Front Command (HFC) conduct a comprehensive, structured evaluation of emergency preparedness in every hospital every two to three years. Aim: To assess the impact of a periodical evaluation on levels of emergency preparedness over time in a level one trauma center. Methods: Evaluation of emergency preparedness is conducted by approximately 12 evaluators from the MOH and HFC, encompassing mass casualty incidents (MCIs), mass toxicological/chemical incidents (MTEs), radiological and biological events, earthquakes and conflicts. Evaluations are based on objective parameters, relayed to hospitals prior to the evaluation. The hospital's level of emergency preparedness is graded and improvements that must be implemented are delineated. The grades of four evaluations conducted from 2011 to 2018 were compared to identify trends in preparedness. Results: Mean levels of emergency preparedness in the 2018 versus 2011 evaluations presented an increase concerning all threats, including MCIs (92 vs. 90), MTEs (99 vs. 77, respectively), biological events (96 vs. 73, respectively), radiological events (91 vs. 79), earthquakes (87 vs. 60, respectively), and conflicts (95 vs. 74). The relative change in levels of preparedness was more noted concerning biological events and earthquakes. Discussion: A periodical evaluation by governing authorities seems to motivate the hospital's administrations to invest efforts in building and maintain a high level of emergency preparedness. Systematic evaluations conducted bi-annually contributed to improved readiness for diverse emergency scenarios, including for threats that less frequently materialize.